Managerial roles and the training of Malaysian co- operatives' managers - Sarif, Suhaimi Mhd; Ismail, Yusof (Co-operative College of Malaysia, 2010)
Managers get things done through people efficiently and effectively. Managerial roles explain the actual work that managers do. Mintzberg has documented ten (10) specific managerial roles and classified them into three areas: (a) interpersonal, (b) informational, and (c) decisional. Managers of conventional companies are governed, among others, by the Companies Act 1965 under the Companies Commission of Malaysia, whereas co-operative organisations are administered by the Co-operative Act 1963 under the supervision of the Co-operative Commission of Malaysia. This paper investigates the perceptions of co-operatives’ senior managers toward managerial roles and their training within the co-operatives’ framework. The results showed that senior managers of co-operatives performed Mintzberg’s managerial roles and sought similar managerial training like their companies counterparts despite operating under different legal frameworks. However, the results were not conclusive considering constraints on sample size of the study (n=52). The study proposed that future research use case study method to understand the details of managerial work at cooperatives.